Design Thinking for Social Innovation - Brown, Tim; Wyatt, Jocelyn (Stanford Social Innovation Review, 2010)
Designers have traditionally focused on enhancing the look and functionality of products. Recently, they have begun using design techniques to tackle more complex problems, such as finding ways to provide low-cost healthcare throughout the world. Businesses were the first to embrace this new approach—called design thinking—and nonprofits are beginning to adopt it too.

Bootcamp Bootleg Design Thinking Toolkit - d.school (Institute of Design, Stanford University, 2010)
Keywords: IMPORTANT

Grounded Theory Method in HCI and CSCW - Muller, Michael J; Kogan, Sandra (IBM Center for Social Software, 2010)

The open book of social innovation - Murray, Robin; Caulier-Grice, Julie; Mulgan, Geoff (Young Foundation & NESTA, 2010)

Innovation, Sustainability, Development: A New Manifesto - STEPS Centre (STEPS Centre, 2010)
Our Manifesto project publication is available in print, on CD or to view online. Innovation, Sustainability, Development: A New Manifesto recommends new ways of linking science and innovation to development for a more sustainable, equitable and resilient future. The multimedia version, with added audio, video and background documents, is available on CD and online.

Analysis of the factors affecting the sustainability of ICT4D initiatives - Marais, Mario (ICT for development: people, policy and practice, 2011)

Design thinking: understand - improve - apply - Plattner, Hasso; Meinel, Christoph; Leifer, Larry (Understanding innovation, 2011)
"In this book, the researchers take a system's view that begins with a demand for deep, evidence-based understanding of design thinking phenomena. They continue with an exploration of tools which can help improve the adaptive expertise needed for design thinking. The final part of the book concerns design thinking in information technology and its relevance for business process modeling and agile software development, i.e. real world creation and deployment of products, services, and enterprise systems"--Cover
Keywords: Creative ability in business; Creative thinking; Designer; Industrial management; Innovation; Organizational change; Product development; System design; Technological innovations

Participatory design with marginalized people in developing countries: Challenges and opportunities experienced in a field study in Cambodia - Hussain, Sofia; Sanders, Elizabeth B.-N.; Steinert, Martin (International Journal of Design, 2012)

Use Case and Requirements Analysis in a Remote Rural Context in Mali - Bon, Anna; de Boer, Victor; Gyan, Nana Baah; van Aart, Chris; De Leenheer, Pieter; Tuyp, Wendelien; Boyera, Stephane; Froumentin, Max; Grewal, Aman; Allen, Mary; Tangara, Amadou; Akkermans, Hans (Requirements Engineering: Foundation for Software Quality, 2013)
[Context & motivation] Few studies have reported on a systematic use case and requirements analysis of low-tech, low-resource contexts such as rural Africa. This, despite the widespread agreement on the importance of Information and Communication Technologies (ICT) for social and rural development, and despite the large number of ICT projects targeting underprivileged communities. [Question/problem] Unfamiliarity with the local context and differences in cultural and educational backgrounds between end-users and software engineers are the challenges for requirements engineering (RE) we encountered. [Principal ideas/results] We describe a systematic approach to RE in developing areas, based on the Living Lab methodology. Our approach is supported by extensive field research and based on co-creation within a multi-disciplinary and multi-cultural team of developers and users. This approach creates a shared understanding of the problem and its local context, and optimizes communication. [Contribution] We illustrate the approach using a case study of web- and voice-based communication services, that we developed for a rural context in Mali.

Design reality gap issues within an ICT4D project: an assessment of Jigawa State Community Computer Center - Kanya, Rislana Abdulazeez; Good, Alice (Sixth International Conference on Information and Communication Technologies and Development (ICTD2013), 2013)
This paper evaluates the Jigawa State Government Community Computer centre project using the design reality gap framework. The purpose of this was to analyse the shortfall between design expectations and implementation realities, in order to find out the current situation of the project. Furthermore to analyse whether it would meet the key stakeholder’s expectation. The Majority of Government ICT Projects is classified as either failure or partial failure. Our research will underpin a case study of Jigawa State Community Computer centre project. To support our argument we conducted a qualitative case study in which we conducted two interviews, and a survey to find out the current status of the project. Our findings indicated that the project can be classified as a partial failure because few of the centres, operating in some areas of the community, offered socio-economic advancement. Our results also indicated that the project design reality gap is quite significant. This gap occurred due to poor planning and implementation of the project. Our research reveals several challenges that could impact upon the successfulness of the project provide a foundation for further research and add to existing literature. The challenges associated with the project we identify include poor state of power supply, lack of community engagement during the project planning and implementation, lack of commitment from the Local Government Administration. Our research has potential in adding ICT4D literature, reveals how ICT4D project evaluation can be carried out using design reality gap framework and provides guideline for policy makers.

Mapping Context for Social Accountability: A resource paper - O'Meally, Sion C. (The World Bank, 2013)

Perspectives on Participation in Design - Sanders, Elizabeth (Wer gestaltet die Gestaltung? Praxis, Theorie und Geschichte des partizipatorischen Designs, 2013)
Keywords: Design

Routledge international handbook of participatory design - Simonsen, Jesper; Robertson, Toni (Routledge, 2013)
"Participatory Design is about the direct involvement of people in the co-design of the technologies they use. Its central concern is how collaborative design processes can be driven by the participation of the people affected by the technology designed. Embracing a diverse collection of principles and practices aimed at making technologies, tools, environments, businesses, and social institutions more responsive to human needs, the International Handbook of Participatory Design is a state-of-the-art reference handbook for the subject. The Handbook brings together a multidisciplinary and international group of highly recognized and experienced experts to present an authoritative overview of the field and its history and discuss contributions and challenges of the pivotal issues in Participatory Design, including heritage, ethics, ethnography, methods, tools and techniques and community involvement. The book also highlights three large-scale case studies which show how Participatory Design has been used to bring about outstanding changes in different organisations. The book shows why Participatory Design is an important, highly relevant and rewarding area for research and practice. It will be an invaluable resource for students, researchers, scholars and professionals in Participatory Design"--

An analysis of factors influencing success of ICT4D projects: a case study of the Schools Computerisation Programme in Mashonaland West Province, Zimbabwe. - Musiyandaka, Donna; Ranga, Gideon; Kiwa, Jacqueline Fungai (The Journal of Community Informatics, 2013)
Keywords: ICT4D programmes; success factors

Building tech-powered public services - Bickerstaffe, Sarah (Institute for Public Policy Research, 2013)
Given the rapid pace of technological change and take up by the public it is a question of when not if public services become tech powered This new paper asks how we can ensure that innovations are successfully introduced and deployed

Steering E-Government Projects from Failure to Success: Using Design-Reality Gap Analysis as a Mid-Implementation Assessment Tool - Lessa, Lemma; Negash, Solomon; Belachew, Mesfin (Emerging Issues and Prospects in African E-Government:, 2014)
There are many e-government failures in developing countries. Most studies look at these after the event (post hoc), but this chapter takes an original approach to look mid-implementation (durante hoc) in order to provide recommendations for improvement. The authors chose a partial failure/partial success land management information system being implemented in one Ethiopian city. The project has made retrieval of land information quicker and simpler but is only partly implemented, and is still—on occasion—circumvented by public servants for personal gain. They used design-reality gap framework to understand why the project had partly failed. The authors used the design-reality gap analysis to propose an action plan that would help institutionalise the system, steering it from partial failure to success. They demonstrate the value of this framework as a tool for mid-implementation analysis of e-government projects. The authors recommend its usage on other ongoing e-government projects in developing countries.

Adapting lean thinking to market systems development: Principles and practices for donors/funders - Rasmussen, Leanne (Engineers without borders, 2014)
The purpose of this paper is to provide funders and implementers of market systems development (MSD) projects with principles, practices, and structures that enables these projects to thrive. It is based on a book that has sold millions of copies worldwide, and a school of thought taught at institutions such as Harvard Business School and practiced in companies ranging from giants such as Toyota to the most successful tech start-ups in Silicon Valley. Published in 2011, Eric Ries wrote the Lean Startup as a remedy to the countless start-ups that create their own demises by getting started with the wrong goals, the wrong structures, and the wrong processes. He outlines an approach that enables the startup to navigate ambiguity and risk while using resources effectively. The conditions a MSD project faces are remarkably similar to those which a startup business faces; it needs structures and processes that are matched to the unpredictable, complex environment which it is attempting to influence. MSD projects can thus benefit from private-sector thought leadership on how start-ups can situate themselves for success. This paper starts with an overview of lean thinking, a concept that derives from lean manufacturing which is widely accepted as the leading approach to modern manufacturing. It explains how Ries’s Lean Startup adapts these principles, and then it in turn adapts these ideas for market systems development. The following three sections provide an overview of Lean Startup concepts, applying them to the development sector as appropriate. The final section summarizes and makes suggestions on next steps for funders who wish to set MSD projects up for success using a lean approach. Overall, the paper builds a case for how the Lean Startup’s approach can enable MSD projects to work successfully in ambiguity and increase their potential for achieving robust and sustainable results, all while using donor resources more efficiently.
Keywords: Adaptive Development; Lean

Assessing the use of technological tools and strategies by Oxfam Novib partners in Angola, Burundi, Egypt, Niger, Pakistan, Rwanda and Uganda - The Engine Room (2014)
This report presents findings and insights from the Oxfam Novib pilot module of TechScape, which assessed how Oxfam Novib partners in seven countries related to the use of technology in their work. This report does not aim to draw conclusions about the nature of technology use by Oxfam Novib partners per se, or even the partners included in this assessment. The dramatic difference in organizational activities, contexts and objectives are too great for that. Detailed analysis of how partners are relating to technology in their work, and specific recommendations for greater efficiency and impact are presented in the TechScape Country Briefs. This report aims instead: • to describe the context in which the assessments took place, • to propose insights gained from the cumulative process about measurement, learning and capacity development, and • to identify opportunities for Oxfam Novib to pursue capacity development and knowledge sharing between countries and across the network, through mechanisms that minimize resource demands and directly target documented needs.

Probes, toolkits and prototypes: three approaches to making in codesigning - Sanders, Elizabeth B.-N.; Stappers, Pieter Jan (CoDesign, 2014)
The role of making in the design process has been growing, taking on new forms and involving new players over the past 10 years. Where we once primarily saw designers using making to give shape to the future, today we can see designers and non-designers working together, using making as a way to make sense of the future. In this paper, we describe the landscape of design research and practice at the end of 2013 with special attention to the role of making across these perspectives: approach (cultural probes, generative toolkits and design prototypes), mindset (designing for people and designing with people), focus in time (the world as it is, the near future and the speculative future) as well as variations in design intent (provoking, engaging and serving).

DIY - Development Impact and You: Practical Tools to Trigger and Support Social Innovation - Nesta (NESTA, 2014)
Keywords: IMPORTANT

Beyond the Pioneer: Getting inclusive industries to scale - Koh, Harvey; Hedge, Nidhi; Karamchandani, Ashish (Deloitte Touche Tohmatsu India Private Ltd (DTTIPL), 2014)

Beyond 'Technology for Development' and 'Sustainability' towards Systemic and Holistic Rural Innovation: Success Factors from the Southern African Experience over 20 years - Buisson, Uys Du; Cronje, Braam; Marais, Mario; Haruperi, Emmanuel; Rensburg, Johann (2014 International Conference of the UNESCO Chair in Technologies for Development, 2014)
Abstract: This paper describes essential, real-world activities and processes needed to develop and deploy people-centred networks enabled with innovative technologies that in turn produce "...

Time for a Donor Funding Charter? - kiwanja.net (Donor's Chapter, 2014)

Taking Innovations to Scale: Methods, Applications and Lessons - Cooley, Larry; Linn, Johannes F. (R4D, 2014)
The international development community increasingly recognizes the need to go beyond fragmented, one-of projects. In response, there is now much talk and some action on scaling up successful innovations and pilot projects with an explicit goal of achieving sustainable impact at scale. However, many questions remain about the practical implications of pursuing a systematic scaling up approach and about how the approaches being pursued by diferent institutions and practitioners relate to each other.

Scaling up co-design - Dearden, Andrew; Light, Ann; Zamenopoulos, Theodore; Graham, Paula; Plouviez, Emma; de Sousa, Sophia (PDC 2014 : Reflecting connectedness : proceedings of the 13th Participatory Design Conference, 2014)
In this paper we reflect on our experiences in a project where academic researchers and social change organizations are working together to explore how participatory and co-design practices can be disseminated and spread within the 'third sector'. The research project is itself co-designed and co-produced, but within various constraints arising from research funding models. We explore both our immediate outputs and our learning about successful co-research models for this challenge.

Can policy-makers think like designers? - Adler, Natalia (A workshop on Doing Development Differently, 2014)
This is the poster used by Natalia Adler, from Unicef, at the Doing Development Differently workshop in 2014. Can policy-makers think like designers? Since 2012, UNICEF has been supporting two autonomous governments in Nicaragua to develop empathy-driven policies for children. While policies are the final product, the goal of the Designing for Children Initiative is to make government officials think like designers. A good policy or service is nothing without active and engaged frontline workers. From the onset, our objective was to transform public employees into ‘public entrepreneurs.’ In doing so, we have disrupted the traditional assumptions about participatory governance, where it normally suffices to hold a meeting and have people talk about their needs and aspirations. For participation to work, government officials have to relearn how to listen. They have to let go of pre-determined assumptions and their expert status, and put themselves in the shoes of the people they are trying to reach. This is the process of empathy-driven policy-making. For the past two years, we have used a Human Centered Design (HCD) approach to make this happen. While HCD is often seen as an innovation in itself, for us, it’s just a means to an end: common-sense development.

Social Design and Neocolonialism - Janzer, Cinnamon L.; Weinstein, Lauren S. (Design and Culture, 2014)
This article examines the current field of social design: its claims, practices, and methodologies. Findings discovered through qualitative research illuminate the current application of social design practices and offer critique around their use in the social sphere. This article argues that designers must be sensitive to a variety of complex social and cultural cues and structures or they risk contributing to, or practicing, design neocolonialism. The article offers two key theoretical suggestions to further the emerging field's progress. First, social design must shift its focus from one that is human-centered to one that is situation-centered. Second, it is imperative that social design develops a shared framework for understanding, executing, and evaluating its initiatives and interventions. Additionally, this article introduces a matrix to serve as an early iteration of a shared framework.
Keywords: Design Methodology; Design Thinking; Framework; Human-centered design; IMPORTANT; social design

Stop Trying to Save the World: Big ideas are destroying international development - Hobbes, Michael (New Republic, 2014)
Gives some examples of poorly designed interventions (e.g. The play pump)

Sustainability and Value through Improved Decision-making - Meyer, Isabel; Marais, Mario (Designing and implementing an Information and Communication Technology for Rural Education Development (ICT4RED) initiative in a resource-constrained environment: Nciba school district, Eastern Cape, South Africa, 2014)

The field guide to human-centered design: design kit - IDEO (IDEO, 2015)
Keywords: Design; IMPORTANT; Methode

Before the Backlash, Let’s Redefine User-Centered Design - Lee, Panthea (Stanford Social Innovation Review, 2015)
We must better understand user-centered design’s limitations—not just its strengths—in the context of international development. And we must adapt it from its original uses designing commercial products to solving for social good.

ICT4D and Sustainability - Marais, Mario (The International Encyclopedia of Digital Communication and Society, 2015)

The Promise of Lean Experimentation - Murray, Peter; Ma, Steve (Stanford Social Innovation Review, 2015)
By adopting a model from business, nonprofit organizations can launch, test, and implement new programs and services more efficiently. Includes magazine extras.
Keywords: IMPORTANT

Meant to Keep Malaria Out, Mosquito Nets Are Used to Haul Fish In - Gettleman, Jeffrey (The New York Times, 2015)
Nets like his are widely considered a magic bullet against malaria — one of the cheapest and most effective ways to stop a disease that kills at least half a million Africans each year. But Mr. Ndefi and countless others are not using their mosquito nets as global health experts have intended. Nobody in his hut, including his seven children, sleeps under a net at night. Instead, Mr. Ndefi has taken his family’s supply of anti-malaria nets and sewn them together into a gigantic sieve that he uses to drag the bottom of the swamp ponds, sweeping up all sorts of life: baby catfish, banded tilapia, tiny mouthbrooders, orange fish eggs, water bugs and the occasional green frog

Scaling: Innovations Missing Middle - McClure, Dan; Gray, Ian (ThoughtWorks, 2015)

Managing the Journey to Scale Up Innovation in the Humanitarian and Development Sector - McClure, Dan; Gray, Ian (ThoughtWorks, 2015)

Using Data to Influence Government Decisions. Opportunities and Challenges for User-Centered Design to Improve Governance Data Impact - Reboot (Reboot & OSF, 2015)

Engineering Complex Scaled Up Innovations in the Humanitarian and Development Sector - McClure, Dan; Gray, Ian (ThoughtWorks, 2015)

Design for Sustainability: Countering the Drivers of Unsustainability in Development Projects - Meyer, Isabel; Marais, Mario Alphonso (The Journal of Community Informatics, 2015)
Development projects aim to make a difference in communities. Funders often require that the intervention needs to last, or that it needs to effect change that will last, over an extended period of time. In short, a sustainable difference needs to be made and this is an important measure of success.  However, there are inherent drivers in the combined system of donors and beneficiaries that counter sustainability. This article explores these drivers, and identifies project design elements that need to be in place in order to promote sustainability by countering the drivers. This approach is applied to an education project, and implications for ICT4D projects are developed.
Keywords: Development; Project design; Systems Approaches; sustainability

Implementing Innovation: A User's Manual for Open Government Programs - Reboot Design (2015)
This guide draws from our experience around the world helping government reformers achieve real change. It is a practical resource for anyone working to implement an open government initiative.

The ethical limits of bungee research in ICTD - Dearden, Andrew; Tucker, William D. (2015 IEEE International Symposium on Technology and Society, 2015)
Research in ICTD is difficult because engineers with technical expertise are separated from the challenges that they are trying to address by large physical distances and significant social differences. To overcome these challenges, much research involves occasional short visits by external researchers to developing regions to investigate problems and generate ideas which are then developed back at the engineers' home base before further return visits for deployment and evaluation. This paper highlights the ethical limitations of this `bungee research', and reflects on our experiences in evolving more fruitful research practices. We argue that relying on bungee research as a primary model of research engagement is unethical, and we suggest some minimal conditions that are necessary, but not sufficient, for such visits to be ethically defensible in ICTD research.

Leading Change Through Adaptive Design - Berstein, Maya; Linsky, Marty (Stanford Social Innovation Review, 2016)
By integrating two practices—design thinking and adaptive leadership—social innovators can manage projects in a way that’s both creatively confident and relentlessly realistic.

Scaling up - From Vision to Large-Scale Change - A Management Framework for Practitioners - Cooley, Larry; Kohl, Richard; Ved, Rajani R. (MSI, 2016)
This document was originally published in 2006 and re-issued in a substantially revised Second Edition in 2012.

Measuring the Barriers to Big Data for Development: design-reality gap analysis - Fernando Gomez, L.; Heeks, R. (Manchester University Development Informatics Working Paper Series, 2016)

Open Policy Making toolkit - gov.uk (2016)
This manual includes information about Open Policy Making as well as the tools and techniques policy makers can use to create more open and user led policy.

Winners and Losers in the Global App Economy - Pon, Bryan (2016)

How ICT4D Research Fails the Poor - Harris, Roger W. (Information Technology for Development, 2016)
Research can improve development policies and practices and funders increasingly require evidence of such socioeconomic impact from their investments. This article questions whether information and communication technologies for development (ICT4D) research conforms to the requirements for achieving socioeconomic impact. We report on a literature review of the impact of research in international development and a survey of ICT4D researchers who assessed the extent to which they follow practices for achieving socioeconomic impact. The findings suggest that while ICT4D researchers are interested in influencing both practice and policy, they are less inclined toward the activities that would make this happen, especially engaging with users of their research and communicating their findings to a wider audience. Their institutions do not provide incentives for researchers to adopt these practices. ICT4D researchers and their institutions should engage more closely with the users of their research through more and better communications with the public, especially through the use of information and communication technologies.
Keywords: ICT4D; Policy making; Practice; Research; impact

From principle to practice: Implementing the Principles for Digital Development - Waugaman, Adele (2016)
The Principles for Digital Development (download PDF here) find their roots in the efforts of individuals, development organizations, and donors alike who have called for a more concerted effort by donors and implementing partners to institutionalize lessons learned in the use of information and communication technologies (ICTs) in development projects.
Keywords: IMPORTANT

A Critique of the Claims About Mobile Phones and Kerala Fisherman. The Importance of the Context of Complex Social Systems - Steyn, Jacques (The Electronic Journal of Information Systems in Developing Countries, 2016)
This paper challenges some fundamental aspects of research and conclusions relating to the use of technology for community development. Views of technology, in this case the mobile phone, as a tool for increased economic welfare are often skewed due to extreme reductionism, ambiguous interview questions and poor data sources. Research of complex social systems or sub-systems give the wrong answers when reductionist methodologies are used. To demonstrate such shortcomings, the 2007 paper of Robert Jensen serves as an example. His conclusion that mobile phones enable Kerala fishermen to increase their economic welfare is the most cited paper on ICT4D topics, but there are fundamental methodological and logical problems with the claim, while other research came to contradictory conclusions. This critique is presented on many levels: ideological, paradigmatic, methodology, logical, statistical and semantic.

Participation in ICT Development Interventions: Who and How? - Thapa, Devinder; Sæbø, Øystein (The Electronic Journal of Information Systems in Developing Countries, 2016)
The aim of participatory development (PD) in the context of using Information and Communication Technologies (ICT) for development (ICT4D) is to empower underprivileged communities and disadvantaged segments of the stakeholders. The literature on ICT4D is replete with empirical evidence showing that ICT interventions often fail since they are often externally initiated, with very limited involvement from the affected (Heeks, 2002). Clearly, the principles and concepts of PD are relevant to ICT4D. However, we should not consider PD a panacea but need to understand the caveats and processes by which PD happens. Questions to ask include: What are the various challenges in PD? Who are the relevant stakeholders? Why and how do actors enrol in the project? How do we create sustainable ICT4D projects through PD? To understand these research questions, we present a case analysis of a project in Nepal called the Nepal Wireless Networking Project (NWNP). Investigating the specific initiatives that they enabled, telemedicine, education and jobs, we propose that the key participants in the NWNP were activist actors and the affected and that activists drew upon existing Social Capital to enrol the affected through a process explained by Actor Network Theory (ANT). In the process, they built other forms of Social Capital, which in turn extended the benefits of PD to several mountain villages.

A Low-resource Aware Framework for ICT Service Development in Rural Africa - Bon, Anna; Gordijn, Jaap; Akkermans, Hans (28th International Conference on Advanced Information Systems Engineering, 2016)
Technological innovation and information & communication technologies (ICTs) are considered enabling factors for social and economic development, even in very poor parts of the world. However,...

Developing ICT Services in a Low-Resource Development Context - Bon, Anna; Akkermans, Hans; Gordijn, Jaap (Complex Systems Informatics and Modeling Quarterly, 2016)
Keywords: IMPORTANT

Moving ICTD research beyond bungee jumping: practical case studies and recommendations - Dearden, Andy; Tucker, William (IEEE Technology and Society Magazine, 2016)
The global spread of Internet and mobile communications has been accompanied by a growing interest in how information and communication technologies (ICTs) can contribute to social and economic development. There are a considerable number of such examples in developing countries. For example, M-Pesa in Kenya allows workers in the cities to send money back to families living in the countryside using SMS messages on basic mobile phones. In Ghana, the Motech project allows community health workers to use feature phones and network services to track ante-natal (and post-natal) care with the objective of improving outcomes for both mothers and babies. Other examples include Gram Vaani's (GRINS) open-source software for community radio stations, or Ushahidi's initiatives, which began with tracking post-electoral violence in Kenya in 2008 using mobile phones and Google maps. These examples illustrate different ways of leveraging ICT to improve lives and livelihoods worldwide. Such stories are inspiring many young (and not so young) researchers and innovators alike to explore how technology might support social and economic development and inclusion in global knowledge exchange

Grow - Scale - Impact: How to help inclusive business achieve scale - Pérez Castro, Andrea A.; Tora, Krisztina (GIZ, 2016)

Design Thinking is not enough – Innovate DFID - DFID, Innovate (Medium, 2016)
By Tamara Giltsoff

Scaling Assessment Map: An Evolving Tool Supporting Innovation Scale Up - McClure, Dan; Gray, Ian (ThoughtWorks, 2016)
Nearly three years ago we wrote about the “Missing Middle” in the innovation lifecycle[i], a gap that kept successful pilot programs from reaching the goal of replication and optimization in multiple contexts. Since then, scaling humanitarian innovation has received a great deal of attention from the sector, with a number of new initiatives specifically focused on the scaling challenge.

Scaling accountability through vertically integrated civil society policy monitoring and advocacy - Fox, Jonathan (MAVC Working Paper, 2016)
This working paper argues that the growing field of transparency, participation and accountability (TPA) needs a conceptual reboot, to address the limited traction gained so far on the path to accountability. To inform more strategic approaches and to identify the drivers of more sustainable institutional change, fresh analytical work is needed. This paper makes the case for one among several possible strategic approaches by distinguishing between “scaling up” and “taking scale into account”. This proposition grounds an explanation of the vertical integration strategy, which involves multi-level coordination by civil society organisations of policy monitoring and advocacy, grounded in broad pro-accountability constituencies. To spell out how this strategy can empower pro-accountability actors, the paper contrasts varied terms of engagement between state and society, proposing a focus on collaborative coalitions as an alternative to the conventional dichotomy between confrontation and constructive engagement. The paper grounds this discussion by reviewing the rich empirical terrain of existing multi-level approaches, summarizing nine cases – three each in three countries – to demonstrate what can be revealed when TPA initiatives are seen through the lens of scale. It concludes with a set of broad analytical questions for discussion, followed by testable hypotheses proposed to inform future research agendas

18F Method Cards - A collection of tools to bring human-centered design into your project - 18F-GSA (18F-GSA, US Governement, 2017)
18F’s method cards describe how our organization puts human-centered design into practice.

Development is Going Digital: What is the role of INGOs? ICT for Development programmes in the Horn, East and Central Africa - Haikin, Matt; Flatters, George (Policy & Practice, 2017)
Development is going digital and INGOs like Oxfam have a vital convening role to play. This paper draws on ICT for Development in Oxfam’s programmes in the Horn, East and Central Africa to consider what this role is.  In order to realise the opportunities

Project Cycle Hacker's Toolkit - changing the conversation around your projects - UNDP (UNDP, 2017)
The Istanbul Regional Hub partnered with Nesta and 4 country offices (fYR Macedonia, Moldova, Georgia and Kyrgyzstan) to develop a program that can help us bring innovation closer to the center of the organization by embedding it in the key project management business processes - The Project Cycle Hackers Toolkit.

Critical agency and development: applying Freire and Sen to ICT4D in Zambia and Brazil - Poveda, Sammia; Roberts, Tony (Information Technology for Development, 2017)
(2017). Critical agency and development: applying Freire and Sen to ICT4D in Zambia and Brazil. Information Technology for Development. Ahead of Print. doi: 10.1080/02681102.2017.1328656

From Design Thinking to Systems Change - Conway, Rowan; Masters, Jeff; Thorold, Jake (RSA, 2017)
This report takes the Small Business Research Initiative (SBRI), a twophase pre-procurement innovation programme that aims to match social challenges with new ideas, as its primary case study. It suggests augmenting the excellent design thinking deployed through SBRI with a think like a system, act like an entrepreneur lens in order to drive better social outcomes from SBRI-originating innovations. Programmes like SBRI have great potential to drive change and address pressing challenges, but must be guided by a more developed understanding of how change happens. The stakes are too high to not raise our game when it comes to social innovation. Wicked problems can be overcome but will require sophisticated theories of change able to account for the complexity and unpredictability of modern life. We offer think like a system, act like an entrepreneur as a contribution to this effort. This report is based on the following research: •• Desk based review of relevant literature; •• A series of structured interviews with participants in SBRI competitions; and •• An expert round table that brought together policymakers, commissioners, procurement experts and entrepreneurs to consider and develop initial findings.
Keywords: ⛔ No DOI found

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (MAVC Research Report, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

An introduction to systems thinking and tools for systems thinking - Allen, Will; Kilvington, Margaret (Learning fro Sustainability, 2018)
Systems thinking is an approach to integration that is based on the belief that the component parts of a system will act differently when isolated from the system’s environment or other parts of the system. THIS PAGE PROVIDES PLENTY OF RESOURCES ON SYSTEM THINKING

Follow the rabbit: Field Guide to Systemic Design - CoLab (Government of Alberta, 2018)
This Field Guide is designed to support budding systemic designers to facilitate and lead systemic design projects. It’s designed for systemic designers who have basic familiarity with SD concepts and are looking for some practical tips and tools to put theory into action. While this Guide was designed with Government of Alberta staff in mind, the content applies across a range of issue areas, sectors, and intersections. The Guide goes through a systemic design project from concept to implementation. It takes you through the workshop planning process, and discusses workshop roles and client relations. In the FAQs, you’ll find explanations to some commonly asked questions about systemic design concepts to help you introduce others to SD and bring them along with you. You’ll get the most out of this field guide if you approach it with a systemic design mindset – open, willing to try things, a desire to learn, and a ‘yes, and’ orientation. Think of this field guide as an early stop in your systemic design journey: it’s not the end of your learning – it’s a jumping off point. In the Additional Resources section, you can connect to more in-depth explorations of concepts and practical applications.

Principles for Digital Development - digitalprinciples.org (2018)

The landscape of innovation approaches - Leurs, Bas (States of Change, 2018)
An overview of innovation methods and approaches we’ve come across in government innovation practice.

States of Change - Learning programme - Nesta (Nesta, 2018)

Innovation lifecycle and the missing middle - Gray, Ian; McClure, Dan (Managing Humanitarian Innovation - The cutting edge of aid, 2018)

Human-Centered, Systems-Minded Design - Both, Thomas (Stanford Social Innovation Review, 2018)
Both human-centered and systems-thinking methods fit within an effective design approach, and can work in conjunction to address social challenges.

Digital Principles into practice - HDIF (HDIF, 2018)

Scaling Up Inclusive Approaches for Marginalised and Vulnerable People - Carter, Becky; Joshi, Anu; Remme, Michelle (2018)
This rapid review summarises the evidence on how to scale up inclusive approaches to complex social change. It looks at how to design scalable inclusive change interventions, as well as how to plan and manage the scale-up process. Focusing on interventions with the aim of reaching the most marginalised and transform social norms, it covers programmes aiming to deliver inclusive outcomes for women and girls (with a particular focus on preventing violence against women and girls) and persons with disabilities. To date, many interventions seeking to change harmful gender and disability norms have been implemented as small-scale projects. There are limited experiences of scale-up and fewer evaluations of these experiences. However, there are some documented case studies as well as emerging analysis that draw out lessons learned. From this evidence base, this rapid desk review identifies eight critical issues commonly highlighted as important considerations when scaling up inclusive change interventions: 1. Opportunities for systemic approach, including integrating political and community-level scale-up, and coordinating across multiple sectors and stakeholders 2. Political support for scale-up 3. Strategic choices: balancing reach, speed, cost, quality, equity, and sustainability 4. Catalysing change: tipping points, diffusion effects, and local champions 5. Locally grounded, participatory, and adaptive approaches 6. Long-term approaches with funding models to match 7. Cost-effective and financially feasible scale-up strategies 8. Measuring impact and sustainability.

Humanitarian Innovation Guide - ELHRA (2018)
The Humanitarian Innovation Guide is a growing online resource to help individuals and organisations define humanitarian problems and successfully develop innovative solutions. ABOUT THE GUIDE The humanitarian sector is investing in exciting innovations, but it is not yet producing a steady pipeline of well-designed solutions that effectively address problems, evidence their impact, and have the potential to be scaled. As stated in a recent independent evaluation of the Humanitarian Innovation Fund (Triple Line, 2017), a review of the innovation ecosystem in 2015 found significant gaps in resources for innovation, including a shortage of guidance on the skills needed to manage successful innovation projects. These findings were echoed in the research carried out to inform this resource. As part of a grant agreement with the European Commission to provide financial and technical support to emerging humanitarian innovations, and in line with our strategic aim to develop the sector’s skills and capabilities in humanitarian innovation, this resource aims to translate our own learning, along with learning from across the sector, into a practical, grounded guide for innovators working in humanitarian contexts. Building on our unique position in the sector, the Humanitarian Innovation Guide is designed to provide targeted support to individuals and organisations attempting to develop innovative solutions to the challenges facing humanitarian assistance, resulting in a more effective humanitarian response. The Guide is written with two audiences in mind: humanitarian practitioners who are seeking to develop a new approach to their work and want to apply an innovation lens to solving problems; and social entrepreneurs from outside the sector who have identified an opportunity to engage with the sector and need a humanitarian framework to contextualise their innovation plans. We also hope that it will be a useful resource for innovation managers who are tasked with supporting innovation in their agencies, labs or networks. As the first step-by-step guide to managing innovation in the humanitarian sector, we hope that its continued development will better enable individuals, organisations and the wider sector to: Plan the activities involved in an innovation process and systematise the management of innovation. Manage a successful innovation project and generate evidence for innovation. Ensure that innovations are developed in an ethical way, with full consideration of risks and responsibilities.

Digital Development: Elements of a Critical ICT4D Theory and Praxis - Bon, Anna; Akkermans, Hans (Springer International Publishing, 2019)
In recent years, critical research literature in ICT4D has grown. It is widely accepted that theory is to inform practice. However, the inverse directionality, practice informs theory, is much less present in ICT4D, including in critical research. In this paper, we discuss ways how ICT4D research and theory may be better informed by practice—in terms of (i) recognizing praxis-oriented research paradigms and integrating their results, (ii) development of foundational theories, (iii) critical analysis of ICT4D emerging policies, and (iv) positioning ICT4D in the wider development debate. This suggests several elements or directions in which critical research has the potential to push current boundaries of ICT4D in terms of content as well as relevance.
Keywords: Action research paradigm; Critical research; Network complexity theory; Principles for Digital Development

Scale Up Sourcebook - Cooley, Larry; Howard, Julie (Scale Up Conference, 2019)
The Scale Up Sourcebook is informed and inspired by the September 2018 conference, Innovations in Agriculture: Scaling Up to Reach Millions, organized by Purdue University, in partnership with the African Development Bank. The Sourcebook consolidates, extends, and disseminates some of the scaling insights presented at the Purdue conference. It is intended as an easy-to-use guidebook targeted to a broad and diverse audience of stakeholders associated with scaling agricultural technologies and innovations to meet the needs of the world’s poor. The Sourcebook has nine chapters: designing with scale in mind; assessing scalability; using commercial markets to drive scaling; financing the transition to scale; creating an enabling environment for scale; tailoring metrics, monitoring, and evaluation to support sustainable outcomes at scale; and the critical role of intermediary and donor organizations. The Sourcebook provides guidance, tips, and examples, along with links and references to additional resources on scale up.

Scaling Impact: Innovation for the Public Good - McLean, Robert; Gargani, John (Routledge, 2019)
Scaling Impact introduces a new and practical approach to scaling the positive impacts of research and innovation. Inspired by leading scientific and entrepreneurial innovators from across Africa, Asia, the Caribbean, Latin America, and the Middle East, this book presents a synthesis of unrivalled diversity and grounded ingenuity. The result is a different perspective on how to achieve impact that matters, and an important challenge to the predominant more-is-better paradigm of scaling. For organisations and individuals working to change the world for the better, scaling impact is a common goal and a well-founded aim. The world is changing rapidly, and seemingly intractable problems like environmental degradation or accelerating inequality press us to do better for each other and our environment as a global community. Challenges like these appear to demand a significant scale of action, and here the authors argue that a more creative and critical approach to scaling is both possible and essential. To encourage uptake and co-development, the authors present actionable principles that can help organisations and innovators design, manage, and evaluate scaling strategies. Scaling Impact is essential reading for development and innovation practitioners and professionals, but also for researchers, students, evaluators, and policymakers with a desire to spark meaningful change.
Keywords: Developing & Emerging Countries

What’s Next for Design Thinking - Cone, Taylor (Medium, 2019)
Thoughts on the future of creative problem-solving from across the industry